2008
DOI: 10.1002/jhm.343
|View full text |Cite
|
Sign up to set email alerts
|

Approach to and management of the acute stroke patient with atrial fibrillation: A literature review

Abstract: Stroke remains an increasing worldwide cause of disability and mortality, and it is the second leading cause of death in industrialized countries. 1 Patients with atrial fibrillation form a unique group with increased risk of cardioembolic stroke.Despite the widespread application of the National Institutes of Health stroke scale and guidelines, 2,3 patients with atrial fibrillation represent a clinically challenging group that deserves a special approach during the acute stroke phase.The mechanism of stroke i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia and is strongly associated with increased risk of morbidity, such as stroke and thromboembolism. 1 Atrial fibrillation is considered an epidemic, affecting 1 -1.5% of the population in the developed world. 2 The risk increases with age, 3 and the prevalence is projected to grow at least three-fold by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia and is strongly associated with increased risk of morbidity, such as stroke and thromboembolism. 1 Atrial fibrillation is considered an epidemic, affecting 1 -1.5% of the population in the developed world. 2 The risk increases with age, 3 and the prevalence is projected to grow at least three-fold by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, without other contraindications, once AF is diagnosed OA should be considered for primary and secondary stroke prevention. Many large prospective randomised trials have shown that OA therapy lowers the risk of thromboembolic stroke by 70% in patients with AF [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Even if these trails did not involve paced subjects, there is no reason for excluding "a priori" them from prophylaxis with cumarins.…”
Section: Discussionmentioning
confidence: 99%
“…AF is a frequent complication of MS. A left atrial mural thrombus is a common finding, particularly in the left atrial appendage, in patients with mitral valve disease and AF. Specifically, patients with MS who develop AF increase their risk of cardioembolism by three to seven times . Therefore, all patients having MS with AF need long‐term anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, patients with MS who develop AF increase their risk of cardioembolism by three to seven times. 8 Therefore, all patients having MS with AF need long-term anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 99%